2000
DOI: 10.3354/meps193181
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and the role of physical processes in the feeding dynamics of two larval sciaenids Sciaenops ocellatus and Cynoscion nebulosus

Abstract: Red drum Sciaenops ocellatus and spotted seatrout Cynoscion nebulosus larvae were collected using plankton and benthic-sled tows every 2 h for 26 h on 4 separate dates in late August to early October 1990 in Aransas Bay, Texas, USA. Gut contents and gut fullness were evaluated to determine if feeding was randomly distributed over depth and time, and to compare feeding between the 2 species. Calanoid copepods were the dominant prey over all size-classes of red drum larvae. Copepod nauplii, bivalve and barnacle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…These authors observed that the maximum size of ingested prey was smaller than the maximum mouth gape size, which suggests that mouth size limits the size of items captured by C. undecimalis juveniles. As such, individuals with larger mouth size are able to ingest larger prey and are therefore not selective for smaller-sized prey (HOLT & HOLT, 2000). This fact explains the presence of small prey also in the diet of larger juveniles, as observed herein.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These authors observed that the maximum size of ingested prey was smaller than the maximum mouth gape size, which suggests that mouth size limits the size of items captured by C. undecimalis juveniles. As such, individuals with larger mouth size are able to ingest larger prey and are therefore not selective for smaller-sized prey (HOLT & HOLT, 2000). This fact explains the presence of small prey also in the diet of larger juveniles, as observed herein.…”
Section: Discussionsupporting
confidence: 65%
“…Juveniles, in contrast, showed greater amplitude in food item size, indicating that the size of ingested prey increases in larger predators, whereas the minimum size of ingested prey changes little for a wide range of predator sizes (SCHARF et al, 2000). The intake of small prey by different size classes and an increasing variation in prey size with growth has been recorded for other carnivore species (HOLT & HOLT, 2000). According to MAGNHAGEN & HEIBO (2001), predator mouth gape size and prey body height are the main factors that determine whether a piscivore with limited gape size can ingest its prey.…”
Section: Discussionmentioning
confidence: 94%
“…Ichthyoplankton surveys commenced within 48 h of each new and full moon, times of elevated sciaenid spawning activity in the southeastern USA (Peters & McMichael 1987, McMichael & Peters 1989. Most surveys (44 of 48) were conducted at night because sciaenid larvae (and many other taxa) exhibit a fairly uniform distribution in the water column at this time (Holt & Holt 2000). Eight ichthyoplankton tows were made within most subbasins on each survey with locations chosen using a random point generator in Arcview 3.2 GIS software.…”
Section: Methodsmentioning
confidence: 99%
“…Food for fish larvae is usually determined by fish mouth size, prey size and fish ability to prey, which suggests that small prey with slow swimming, such as ciliate and dinoflagellate protozoa would be more suited GALLAGER, 2000, HUNT VON HERBING et al, 2001). In the majority of marine fish larvae, especially the ornamental ones, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their abundance and size -similar or even smaller than nauplii of copepods, probably they occupy an important position on aquatic trophic food web. According to Holt and Holt (2000), marine fish larvae in the wild commonly feed on a large array of microzooplankton, including protozoa (tintinnid and ciliates), dinoflagellates, larvae of mollusks and, mainly, eggs and nauplii of copepods. However, there are few studies on their role as source of live food in the early stages of fishes and invertebrates (KRAUL, 2006 apud CÔRTES;TSUZUKI, 2012, OLIVOTTO et al, 2005THOMPSON et al, 1999).…”
Section: Introductionmentioning
confidence: 99%